Development of durian peel activated carbon for the removal of cod and colour from semi-aerobic landfill leachate. - Kamaruddin, Mohamad Anuar (2011)
Pencemaran larut lesapan adalah masalah utama yang di hadapi oleh pihak pengurusan tapak pelupusan sampah kerana pembuangan larut lesapan tanpa rawatan yang sesuai akan mengancam hidupan akuatik dan manusia. Leachate pollution has been a major problem in landfill management since discharging of it without proper treatment could cause hazard to aquatic life and human being.